Horizontal gene transfer and silver nanoparticles production in a new Marinomonas strain isolated from the Antarctic psychrophilic ciliate Euplotes focardii - John M. S.; Nagoth J. A.; Ramasamy K. P.; Ballarini P.; Mozzicafreddo M.; Mancini A.; Telatin A.; Lio P.; Giuli G.; Natalello A.; Miceli C.; Pucciarelli S. (Scientific Reports, 2020)
We isolated a novel bacterial strain from a prokaryotic consortium associated to the psychrophilic marine ciliate Euplotes focardii, endemic of the Antarctic coastal seawater. The 16S rDNA sequencing and the phylogenetic analysis revealed the close evolutionary relationship to the Antarctic marine bacterium Marinomonas sp. BSw10506 and the sub antarctic Marinomonas polaris. We named this new strain Marinomonas sp. ef1. The optimal growth temperature in LB medium was 22 °C. Whole genome sequencing and analysis showed a reduced gene loss limited to regions encoding for transposases. Additionally, five genomic islands, e.g. DNA fragments that facilitate horizontal gene transfer phenomena, were identified. Two open reading frames predicted from the genomic islands coded for enzymes belonging to the Nitro-FMN-reductase superfamily. One of these, the putative NAD(P)H nitroreductase YfkO, has been reported to be involved in the bioreduction of silver (Ag) ions and the production of silver nanoparticles (AgNPs). After the Marinomonas sp. ef1 biomass incubation with 1 mM of AgNO3 at 22 °C, we obtained AgNPs within 24 h. The AgNPs were relatively small in size (50 nm) and had a strong antimicrobial activity against twelve common nosocomial pathogenic microorganisms including Staphylococcus aureus and two Candida strains. To our knowledge, this is the first report of AgNPs biosynthesis by a Marinomonas strain. This biosynthesis may play a dual role in detoxification from silver nitrate and protection from pathogens for the bacterium and potentially for the associated ciliate. Biosynthetic AgNPs also represent a promising alternative to conventional antibiotics against common pathogens.